Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 70795 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Araneae", { "or" : [ "Country is Brazil", "Country is Argentina", "Country is Uruguay", "Country is Peru", "Country is Chile", "Country is Paraguay", "Country is Colombia", "Country is Bolivia (Plurinational State of)", "Country is Ecuador", "Country is Venezuela (Bolivarian Republic of)", "Country is French Guiana", "Country is Suriname" ] } ] } The dataset includes 70795 records from 54 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000916-150721130643939/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences